Prophylactic effect of edible bird's nest on acetaminophen-induced liver injury response in mice model - Muhammad-Azam, Fazil; Nur-Fazila, Saulol Hamid; Raslan, Ain-Fatin; Noordin, Mohamed Mustapha; Yasmin, Abd Rahaman; Yimer, Nurhusien (Pakistan Journal of Pharmaceutical Sciences, 2022)
Edible bird's nest (EBN) is one of the natural products believed to pose health-enhancing properties. To provide a better insight into the protective role of EBN from a toxicological perspective, acetaminophen (APAP) as a common hepatotoxicant is chosen. This study focuses on the regenerative response of prophylaxis EBN extract in APAP-induced liver injury (AILI) of mice model. Eighty (80) ICR mice were assigned to groups of control, APAP (500 mg/kg), silymarin (200 mg/kg), and prophylactic EBN (60, 120 and 250mg/kg). The EBN and silymarin were orally administered daily for 7 days followed by an APAP intraperitoneal induction. Animals were sacrificed at 5, 10 and 24 hours post-APAP dosing (hpd). Liver samples were processed for hematoxylin and eosin (H&E) staining and proliferating cell nuclear antigen (PCNA) immunostaining. Significant differences in histological changes between APAP and prophylactic EBN groups were observed at 10 hpd with complete liver recovery for all groups at 24 hpd except for EBN 250 that continuously showed injuries. Hepatocyte proliferation was initiated at 5 hpd in EBN 60 and 120, while at 24 hpd, EBN 120 and 250 expressed higher PCNA-stained hepatocytes. The hepatoprotective role of EBN was shown earlier in EBN 60 and 120, while cellular proliferation delay in EBN 250. In conclusion, EBN has the potential as a prophylactic liver supplement to accelerate hepatic regeneration in the AILI model.